2017
DOI: 10.1371/journal.pone.0187726
|View full text |Cite
|
Sign up to set email alerts
|

Dietary amino acid and vitamin complex protects honey bee from immunosuppression caused by Nosema ceranae

Abstract: Microsporidium Nosema ceranae is well known for exerting a negative impact on honey bee health, including down-regulation of immunoregulatory genes. Protein nutrition has been proven to have beneficial effects on bee immunity and other aspects of bee health. Bearing this in mind, the aim of our study was to evaluate the potential of a dietary amino acid and vitamin complex “BEEWELL AminoPlus” to protect honey bees from immunosuppression induced by N. ceranae. In a laboratory experiment bees were infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 79 publications
10
95
1
1
Order By: Relevance
“…ceranae is thought to be a serious threat to the beekeeping industry, but dramatic colony losses were clearly attributed exclusively to N. ceranae infections in some regions only [124][125][126]. N. ceranae as a sole stressor showed suppressive effects on immunerelated genes (Figure 8) in laboratory experiments [127][128][129]. However, in all pieces of research there was a time-dependent inconsistence in gene expression.…”
Section: Infestation With Varroa Destructor and Mixed Virus Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…ceranae is thought to be a serious threat to the beekeeping industry, but dramatic colony losses were clearly attributed exclusively to N. ceranae infections in some regions only [124][125][126]. N. ceranae as a sole stressor showed suppressive effects on immunerelated genes (Figure 8) in laboratory experiments [127][128][129]. However, in all pieces of research there was a time-dependent inconsistence in gene expression.…”
Section: Infestation With Varroa Destructor and Mixed Virus Infectionsmentioning
confidence: 99%
“…The use of supplements with sugar syrup should not be avoided, since they provide suffi cient amino acids, peptides, micro-and macroelements which are absent from pure sugar syrup [18]. The use of supplements may prevent energetic, immune and oxidative stress in bees, and thus prevent losses in apiaries [129,[171][172][173][174]. The presence of a young, healthy bee queen in the hive guarantees the development of healthy bee colonies and successful beekeeping [131,175].…”
Section: General Management In the Apiarymentioning
confidence: 99%
“…Nutrient quality and quantity also affects host immunity through direct and indirect effects mediated by the host's microbiota and pathogen populations (Ponton et al, 2013). Many studies have demonstrated the role of nutritionally linked immunity in countering viruses and other pathogens such as the intracellular microsporidian parasite Nosema (Basualdo et al, 2014;DeGrandi-Hoffman and Chen, 2015;DeGrandi-Hoffman et al, 2010;Glavinic et al, 2017;Xu et al, 2013;Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also pointed toward a connection between protein metabolism and Nosema sp. Holt et al, 2013;Vidau et al, 2014;Glavinic et al, 2017;Li et al, 2019). In addition, Nosema has also been shown to affect gene expression in the brain (McDonnell et al, 2013;Doublet et al, 2016).…”
Section: Effects Of Parasitic Stress From Nosema Ceranaementioning
confidence: 99%